Developing Malaysian tourism and hospitality graduates competency index - Mohd Shariff, Nurhazani; Mohd Nor, Nor Ashikin; Zainol, Noor Azimin; Kayat, Kalsom (2014)
The current study develops an index of tourism and hospitality graduates competencies specifically for the case of Malaysian graduates. The process involved four major stages begins with the competencies generation from the literature search, follows by the competencies verification, then the test for reliability and finally the index development.The competencies generation ended up with 73 competencies while the verification which involved 30 experts in the tourism and hospitality industry indicated 40 competencies to be further tested.The reliability test involved a pilot study of 116 respondents and the findings indicated all competencies have high alpha value above 0.5 and were included to be tested for factor analysis in the index development stage.The index of Malaysian tourism and hospitality graduates‘ competencies consists of eight domains namely Management and Technology Competencies, Leadership Competencies, Organizational Competencies, Personal Effectiveness Competencies, Business-Oriented Competencies, Self-Oriented Competencies, Customer Related Competencies and Innovative Competencies. The index has gone through a systematic process in developing such a tool and significantly contributes to the identification and selection of quality graduates to serve within the tourism and hospitality environment.